2011
DOI: 10.1107/s1600536811037135
|View full text |Cite
|
Sign up to set email alerts
|

(2E)-1-(5-Chlorothiophen-2-yl)-3-(2,3-dimethoxyphenyl)prop-2-en-1-one

Abstract: In the title compound, C15H13ClO3S, the chloro­thio­phene and dimeth­oxy­phenyl groups are linked by a prop-2-en-1-one group. The C=C double bond exhibits an E conformation. The mol­ecule is non-planar, with a dihedral angle of 31.12 (5)° between the chloro­thio­phene and dimeth­oxy­phenyl rings. The meth­oxy group at position 3 is coplanar with the benzene ring to which it is attached, with a C—O—C—C torsion angle of −3.8 (3)°. The meth­oxy group attached at position 2 of the benzene ring is in a (+)synclinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The packing diagram of 4M1PMS and 4BPMS molecules were generated by using MERCURY software [32] and ORTEP diagram of atomic labelled molecules (4M1PMS and 4BPMS) with 50% probability were shown in figures 5(a) and (b). The bond length between C14=C15 is 1.312 (5) Å (4M1PMS) and C14=C15 (-CH=CH-) is 1.326(4) Å (4BPMS) [ figure 5] have good agreement with reported chalcone derivative materials [18][19][20][21][22]33].…”
Section: Single Crystal Xrdsupporting
confidence: 81%
“…The packing diagram of 4M1PMS and 4BPMS molecules were generated by using MERCURY software [32] and ORTEP diagram of atomic labelled molecules (4M1PMS and 4BPMS) with 50% probability were shown in figures 5(a) and (b). The bond length between C14=C15 is 1.312 (5) Å (4M1PMS) and C14=C15 (-CH=CH-) is 1.326(4) Å (4BPMS) [ figure 5] have good agreement with reported chalcone derivative materials [18][19][20][21][22]33].…”
Section: Single Crystal Xrdsupporting
confidence: 81%
“…The SHG conversion efficiency of the compound was measured by powder technique [19] using Nd:YAG laser of wavelength 1064 nm and beam energy was 4 mJ/pulse. The compound did not show SHG efficiency may be attributed to the fact that it crystallizes with inversion symmetry as revealed from single crystal X-ray diffraction study reported by us earlier [15].…”
Section: Linear and Nonlinear Optical Studiesmentioning
confidence: 94%
“…The laboratory grown crystals of CTTMP are shown in Figure 3. The morphology of the CTTMP single crystal was indexed using the single crystal X-ray diffraction data reported [15] in the literature as input to the morphology indexing computer program (WinXMorph) [16]. The indexed morphology of CTTMP is shown in Figure 4.…”
Section: Methodsmentioning
confidence: 99%
“…For compound (VIII) (Vepuri et al, 2012), which provides a genuine example of Z 0 = 2 in space group Cc (Baur & Kassner, 1992;Marsh, 1997Marsh, , 2004, there are no significant direction interactions in the structure: in particular there are neither C-HÁ Á ÁO hydrogen bonds nor short BrÁ Á ÁBr contacts. Compounds (IX) (Prabhu et al, 2011b) and (X) (Prabhu et al, 2014) are isostructural, and (X) was described as forming chains built from two independent C-HÁ Á ÁO hydrogen bonds. However, one of these contacts involves a methyl C-H bond and the other has a C-HÁ Á ÁO angle of only 130 (cf.…”
Section: Database Surveymentioning
confidence: 99%
“…For the sake of clarity, the H atoms and the unit-cell outline have been omitted. The original atomic coordinates (Prabhu et al, 2011b) have been used and the S atom marked with an asterisk (*) is at the symmetry position (Àx + 2, Ày + 2, Àz + 2).…”
Section: Synthesis and Crystallizationmentioning
confidence: 99%